Pengaruh Ukuran Perusahaan dan Solvabilitas terhadap Audit Delay dengan Profitabilitas sebagai Variabel Moderasi pada Perusahaan Manufaktur - Dwi Fitrianingsih; Roza Mulyadi (JURNAL AKUNTANSI DAN MANAJEMEN, 2023)
This research was conducted to determine the effect of company size and solvency onaudit delay with profitability as a moderating variable in food and beverage sub-sectormanufacturing companies listed on the IDX for the 2016-2021 period. This type of research isquantitative, with data collection techniques through secondary data including annual reports onmanufacturing companies in the food and beverage sub-sector. The sampling technique used apurposive sampling method using the specified criteria, a sample of 102. The data analysis techniqueused a moderating effect with Structural Equal Modeling (SEM) through the Partial Least Square(PLS) program. The results of statistical analysis show that firm size has no significant effect on audit delay, the solvency construct has no significant effect on audit delay, Profitability moderatesthe effect of firm size has no effect on audit delay, and the solvency moderating construct has nosignificant effect on audit delay in manufacturing companies the food and beverage sub-sector listedon the Indonesia Stock Exchange for the 2016-2021 period.